Rupture probability of porcine liver under planar and point loading. (20th September 2016) - Arndt, Susann; Russell, Alexander; Tomas, Jürgen; Müller, Peter; Shekhar, Shishir; Brandstädter, Knut; Bruns, Christiane; Wex, Cora
Abstract: At in vivo contacts with operational and surgical instruments, intra-abdominal organs are mechanically stressed to varying degrees. Owing to the distributed mechanical constitutive properties (such as stiffness and strength) of abdominal organs and the usage of different types of surgical instruments which may create unique contacts, the transmitted load on the organ may often be substantially sufficient to cause tissue damage or initiate rupture. Thus, characterization of the rupture probability with respect to different loading conditions is an inevitable necessity to prevent damage of organs during surgical procedures. In this article, measurements of the material behavior (upon loading until failure) of whole porcine livers as well as cut samples in vitro using quasi-static uniaxial compression and indentation tests are presented. The measured force–displacement responses have been approximated using the first-order Mooney–Rivlin constitutive model and thereby, the characteristic hyperelastic mechanical properties have been determined. Using lognormal and Weibull distributions, a comparison of the rupture probability functions of the loading force, the contact displacement, the contact strength and the volumetric toughness at uniaxial compression and indentation are presented. It is shown that larger loads and correspondingly higher deformation work are necessary to initiate rupture in the liver by uniaxial compression (planar loading) in comparison to indentation (almost point loading). Besides the experimental results, finite element method based simulations which describe the stress distribution, sample deformation and sample slipping due to frictional effects are presented. Further aspects such as histological image analysis of ruptured samples, prediction of the rupture origin as well as rupture path propagation are presented.